Chapter A solidariedade entre os povos e Estados da Europa como base da «construção europeia» - Gonçalves, José Renato (Libere carte, 2023)
Starting with the reflection on solidarity as the true and concrete element of the European Union, this article aims to reflect on the solidarity between people and states of Europe as the basis of the European construction.